A color vision approach based on the autoencoder technique and deep neural networks for reconstructing color images under various lighting conditions - Faisal, Asm; Ahmad, Ashhab; Tazwar, Asif (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.